2005
DOI: 10.1128/mcb.25.17.7900-7916.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RelB Expression during the Initiation of Dendritic Cell Differentiation

Abstract: The transcription factor RelB is required for proper development and function of dendritic cells (DCs), and its expression is upregulated early during differentiation from a variety of progenitors. We explored this mechanism of upregulation in the KG1 cell line model of a DC progenitor and in the differentiation-resistant KG1a subline. RelB expression is relatively higher in untreated KG1a cells but is upregulated only during differentiation of KG1 by an early enhancement of transcriptional elongation, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 67 publications
3
20
0
Order By: Relevance
“…Incubation of KG-1 cells with IL-18 (10 ng/mL) for up to 32 h only modestly affected cell viability (12.0% F 2.1% reduction of viability by IL-18 versus unstimulated control after 32 h, n = 4, this trend did not reach statistical significance). We also observed the induction of the transcription factor RelB by IL-18 (10 ng/mL, 4 h; data not shown) confirming that IL-18 is able to initiate processes that are associated with KG-1 cell differentiation towards a dendritic phenotype (24). To investigate a potential role for endogenous IL-18, Western blot analysis was done and revealed that KG-1 cells express clearly detectable levels of pro-IL-18, which are at least similar to those seen in monocytic THP-1 cells (Fig.…”
Section: Induction Of Ifn; By Il-18 In Kg-1cellssupporting
confidence: 49%
“…Incubation of KG-1 cells with IL-18 (10 ng/mL) for up to 32 h only modestly affected cell viability (12.0% F 2.1% reduction of viability by IL-18 versus unstimulated control after 32 h, n = 4, this trend did not reach statistical significance). We also observed the induction of the transcription factor RelB by IL-18 (10 ng/mL, 4 h; data not shown) confirming that IL-18 is able to initiate processes that are associated with KG-1 cell differentiation towards a dendritic phenotype (24). To investigate a potential role for endogenous IL-18, Western blot analysis was done and revealed that KG-1 cells express clearly detectable levels of pro-IL-18, which are at least similar to those seen in monocytic THP-1 cells (Fig.…”
Section: Induction Of Ifn; By Il-18 In Kg-1cellssupporting
confidence: 49%
“…RelB is critical for osteoclastogenesis, because bone marrow macrophages lacking RelB fail to undergo RANKL-mediated osteoclastogenesis in vitro (51). Also, RelB is required for development and function of dendritic cells, and its expression is upregulated during early differentiation (52). RelB was downregulated by IL-3 only on day 7 and not on day 3, suggesting that RelB is required for dendritic cell differentiation on day 3, whereas it is more critical for osteoclast differentiation on day 7.…”
Section: Discussionmentioning
confidence: 93%
“…1F). Because NF-kB and TRAF6 were shown to regulate myelopoiesis and DC subset differentiation (41,47,48) we analyzed whether ectopic miR146a might influence myelopoiesis. Thus, we generated a retroviral expression construct for miR-146a by inserting the genomic sequence of miR-146a 6 250 bp flanking regions into the retroviral vector backbone murine stem cell virus-GFP (Fig.…”
Section: Ectopic Expression Of Mir-146a Does Not Influence Myelopoiesmentioning
confidence: 99%